Bunga Bank dalam Perspektif Tafsir Maudhû’î - Umar Faruq Thohir (Fakultas Ekonomi dan Bisnis Islam, 2017)
For Muslims, the Qur’an is the instruction to meet the needs of absolute life. Rasululullah Sunnah (one of them) serves to explain the content of the Qur’an. There are many verses in the Qur’an and the hadith of the Prophet which encourage people to diligently work (including economic activity) and forbids people to become slacker (Zuhri, 1996: 1). But not every economic activity is justified by the Qur’an, one of them as usury for harming opponents and benefit themselves (alRazi, t.t .: VII: 85).